Sistema de control adaptivo para pacientes con Diabetes Mellitus Tipo 1 - Ríos Ríos, Buenaventura (2004)
The aim of this study is to understand and control type 1 diabetes mellitus, using state theory and algorithms to control Kalman filters. In some northern countries it is acquiring truly epidemic characteristics. All people over 40 years of age, with diabetic ancestors, being overweight or drinking too much liquor, have a tendency to acquire the disease. In fact, diabetes is directly or indirectly responsible for the increase in the death rate in the country, and the existence of a large number of people who are blind or disabled. In Peru, there are approximately one million diabetics, of whom 50% do not know they have the disease and it is estimated that about one in 20 diabetics suffer from Type 1 diabetes mellitus, also known as juvenile or insulin dependent diabetes. In front of it, the scientists of the world are developing different technologies in order to alleviate the disease with diverse results, given its practical applicability, they have been the most used for some decades. Since, theoretically and experimentally, the mathematical differential equation is known that relates to the variables insulin and glucose in the human organism, it is possible to integrate these functions of measurement, control and actuator, in a single implantable electronic device and programmable implantable PIMS Medication System)